Meta-Analysis: The Effect of Ethnoscience-Based Project Based Learning Model on Students' Critical Thinking Skills - Arief Aulia Rahman; Tomi Apra Santosa; Mohammad Edy Nurtamam; Heru Widoyo; Abdul Rahman (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to determine the effect size of ethnoscience-the based project-based learning model on students' critical thinking skills. This type of research is a meta-analysis. Data sources come from 20 national and international journals published from 2015-2023.Â  The search for data sources comes from the google scholar journal database, Eric, ScienceDirect, and ProQuest. The process of selecting data sources using the PRISMA method. Data collection techniques through direct observation and documentation through journal databases. The data analysis technique in this meta-analysis is quantitative statistical analysis with the help of the Comprehensive Meta-Analysis (CMA) version 3.0 application. The results showed an average effect size of 0.827 with high criteria and a standard error of 0.088. This finding shows that the ethnoscience-based Project Based Learning (PjBL) model has a positive effect on students' critical thinking skills.